«Io guardo la placida scena e dipingo». Visioni e cromatismi della natura in Primo vere (1880) - Stagnitti, Barbara (Archivio d’Annunzio, 2023)
Considerably modified and enlarged compared to the 1879 print, the second edition of Primo Vere, the work of Gabriele d’Annunzio’s poetic debut, was published in 1880. This contribution focuses on it, which aims to offer an overview of the representation of nature in its chromatic, musical and olfactory aspects. Portrayed from life or fruit of the imagination, the landscape triumphs in its colouristic value and with its symphonic strength in the alternation of acute, hoarse, powerful or delicate sounds, which sometimes give way to the enchantments of silence or intertwine with the inebriation of fragrances and scents that cloak the atmosphere.